Gezira : a story of development in the Sudan - Gaitskell, Arthur (London : Faber and Faber, 1959)
The Gezira is a triangle of flat land with deep, black soil, between the Blue Nile and the White Nile just south of where these rivers meet at Khartoum. The rainfall is too low and too precarious to grow crops without irrigation-at least, over most of the area. During the period under British control, i.e., up to 1950, the area under irrigation grew to about 1 million acres of which one quarter was producing long-staple cotton. (The irrigated area has been considerably increased under Sudanese
Includes bibliography p. 358-368.
lje 25/01/2018
Loans
Keywords: Agriculture---Development; Rural lands----Development; Gezira (Sudan : Region)